Developing Halal Tourism Based on Local Wisdom in Religious Area of Sis Aljufri - Hanafi, Suhri; Nadia, Nadia; Nurdin, Muhammad Syarif; Nurkhaerah, Sitti; Osman, Zaiton (Indonesian Journal of Halal Research, 2024)
As the country with the largest Muslim population in the world, Indonesia has a substantial opportunity to establish itself as a leading halal tourism destination. However, realizing this potential faces challenges related to the provision of halal facilities and the enforcement of government regulations. This research aims to analyze the development of halal tourism in the Sis Aljufri Religious Area based on local wisdom with reference to the Indonesian Ulema Council halal tourism guidelines. This qualitative research uses Miles and Huberman analysis. The study reveals that the development of halal tourism in this area can be categorized into four aspects: products and services, government support, human resources, and infrastructure. While the development of tourist attractions aligns with the general principles of Sharia tourism and guidelines related to tourists and destinations, facilities such as hotels and travel agencies still need to meet the required Sharia-compliant standards. Overall, the development of halal tourism in the Sis Aljufri Religious Area has shown significant progress, particularly in enhancing products and services, securing government support, and improving infrastructure. However, further efforts are needed to ensure full compliance with the Indonesian Ulema Council’s guidelines, especially in the areas of Sharia hotels and travel agencies, to realize its full potential.